DISRUPTIVE TECHNOLOGY THROUGH SATELLITE IMAGERY BIG DATA IN DISASTER RISK REDUCTION: OPPORTUNITY AND CHALLENGE - Melati, Dian Nuraini (Jurnal Sains dan Teknologi Mitigasi Bencana, 2019)
The development of current massive technology plays an important role in the field of disaster risk reduction and disaster management. In particular, the issue of disruptive technology in which the emerging of new technologies comes with big disruption in many fields. For instance, the development on using satellite imagery big data for disaster management to reduce the disaster risk.The unique characteristics of big data i.e. volume, velocity, and variety stimulate this study to obtain more information on the big data processing and analyze the opportunities and challenges of satellite imagery in the case of disaster risk reduction through literature reviews. The huge amount of data and the ability for real-time analysis provide capabilities on  time series analysis and possitive impact on disaster detection, monitoring, and prediction. However, such technology creates disruption due to the change on using and anlysing the data based on cloud environment. Issues on the technology uses, data security might arise. Nonetheless, the use of satellite imagery big data will remain vastly developed and is able to promote the development of satellite imagery technology.